Blastema formation and periosteal ossification in the regenerating adult mouse digit. Issue 3 (16th October 2018) - Dawson, Lindsay A.; Schanes, Paula P.; Kim, Patrick; Imholt, Felisha M.; Qureshi, Osama; Dolan, Connor P.; Yu, Ling; Yan, Mingquan; Zimmel, Katherine N.; Falck, Alyssa R.; Muneoka, Ken
ABSTRACT: While mammals cannot regenerate amputated limbs, mice and humans have regenerative ability restricted to amputations transecting the digit tip, including the terminal phalanx (P3). In mice, the regeneration process is epimorphic and mediated by the formation of a blastema comprised of undifferentiated proliferating cells that differentiate to regenerate the amputated structures. Blastema formation distinguishes the regenerative response from a scar‐forming healing response. The mouse digit tip serves as a preclinical model to investigate mammalian blastema formation and endogenous regenerative capabilities. We report that P3 blastema formation initiates prior to epidermal closure and concurrent with the bone histolytic response. In this early healing response, proliferation and cells entering the early stages of osteogenesis are localized to the periosteal and endosteal bone compartments. After the completion of stump bone histolysis, epidermal closure is completed and cells associated with the periosteal and endosteal compartments blend to form the blastema proper. Osteogenesis associated with the periosteum occurs as a polarized progressive wave of new bone formation that extends from the amputated stump and restores skeletal length. Bone patterning is restored along the proximal–distal and medial digit axes, but is imperfect in the dorsal–ventral axis with the regeneration of excessive new bone that accounts for the enhanced regenerated bone volume noted in previous studies. Periosteum depletion studies show that this compartment is required for the regeneration of new bone distal to the original amputation plane. These studies provide evidence that blastema formation initiates early in the healing response and that the periosteum is an essential tissue for successful epimorphic regeneration in mammals.